Job strain in public transport drivers: Data to assess the relationship between demand-control model indicators, traffic accidents and sanctions (2018)
This Data in Brief (DiB) article examines the association between theJob Demand-Control (JDC) model of stress and trafficsafetyoutcomes(accidents and sanctions) in public transport drivers (n¼780). Thedata was collected using a structured self-administrable ques-tionnaire composed of measurements of work stress (Job ContentQuestionnaire), and demographics (professional driving experience,hours and days working/driving per week). The data contains 4 parts:descriptive statistics, bivariate correlations between the study vari-ables, analysis of variance (ANOVA) and Post-Hoc comparisonsbetween drivers classified different quadrants of the JDC model. Forfurther information, it is convenient to read the full article entitled“Working conditions, job strain and traffic safety among three groups ofpublic transport drivers”, published in Safety and Health at Work(SHAW)[1](Useche et al., 2018).